Supporting students in higher education in transforming their thesis into a scientific article - Areskoug Josefsson, Kristina; Nordin, Annika (Högre utbildning, 2021)
According to our experience from education in health and welfare, there are increased expectations in academia for students to publish their work as scientific international articles. Reasons and motivation for transforming the thesis to a scientific article vary; however, it is essential to understand that the work includes substantial revision to meet the requirements of a scientific article. We have long experience of teaching in higher education and have supported students from various educational programs in health and welfare to publish their theses as articles in scientific journals. This demands time, engagement and competence from both supervisors and students, demands that to our knowledge rarely are acknowledged in higher education organisations. A coherent guide on how to support students aiming for publication would have been helpful, and this article is anchored in our experiences and reflections on this matter. This article highlights eight preparatory reflective questions and presents a guide for supervisors in supporting actions for the transformation of a thesis to an article.